Creating Voice, Creating Being An Interpretative Phenomenological Analysis of Professional Jazz Musicians’ Experiences (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
In this paper we use an existential theoretical framework to help interpret the experiences of ten professional jazz musicians. Interpretative Phenomenological Analysis (Smith, Jarman and Osborn, 1999) of interviews revealed the psychological dynamics involved in devoting one's life to creating and performing music in a career that can be unstable financially. Through creating their art, the musicians created their being. They described the inter-relational nature of existence, the necessity of having the courage to take risks in their development and overall, indicated that they were engaged in a life-long project of creating a voice they could consider authentic. Critically, the jazz musicians emphasised a high degree of agency as a primary factor in their musical lives. This experience of agency enabled them to sustain their commitment to their project when faced with obstacles that typically undermine a person's motivation to continue on their chosen path.
Keywords: Being; Freedom; Courage; Authentic Voice; Jazz